Application of Impulse Oscillometry Combined with Fractional Exhaled Nitric Oxide in Monitoring Asthma Control Levels in Children - Hu J; Fan Y; Luo R; Li Q; Ai T; Wang L (Journal of Asthma and Allergy)
Jie Hu, Yinghong Fan, Ronghua Luo, Qianqian Li, Tao Ai,* Li Wang* Department of Pediatric Respiratory Medicine, Chengdu Women’s and Children’s Central Hospital, School of Medicine, University of Electronic Science and Technology of China, Chengdu, Sichuan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Tao Ai; Li Wang, Department of Pediatric Respiratory Medicine, Chengdu Women’s and Children’s Central Hospital, School of Medicine, University of Electronic Science and Technology of China, 1617 Riyue Avenue Section 1 Qingyang District, Chengdu, Sichuan, 610000, People’s Republic of China, Tel +8613981931891 ; +8618908015531, Email ait1108@163.com; 625664758@qq.comPurpose: To investigate whether Impulse Oscillometry (IOS) could more effectively monitor children with uncontrolled asthma and evaluate small airway function changes, while establishing a prediction model in combination with fractional exhaled nitric oxide (FeNO) to assist in clinical management and treatment of asthmatic children.Patients and Methods: A retrospective study was conducted on 203 asthmatic children who were followed up in our hospital from August 2023 to August 2024. Patients were divided into controlled asthma group (n=80) and uncontrolled asthma group (n=123). Conventional ventilatory parameters, IOS parameters, FeNO levels, and clinical data were analyzed and compared between the two groups. The optimal prediction model was established through multivariate logistic regression.Results: In the uncontrolled asthma group, the respiratory system impedance at 5 hz (Z5), resistance at 5 hz (R5), the difference between resistance at 5 hz and resistance at 20 hz (R5-R20), resonant frequency (Fres), and FeNO levels were significantly higher compared to the controlled asthma group. The ratio of forced expiratory volume in one second to forced vital capacity (FEV1/FVC), forced expiratory flow at 50% (FEF50), forced expiratory flow at 75% (FEF75), and maximal mid-expiratory flow (MMEF) were lower in the uncontrolled group (P< 0.05). Receiver operating characteristic curve (ROC) analysis demonstrated that Z5, R5, R5-R20, Fres, and FeNO were valuable in asthma diagnosis (P< 0.05), with higher sensitivity in monitoring small airway function compared to MMEF. Multivariate logistic regression analysis established the optimal prediction model combining R5+(R5-R20) +FeNO, with an area under curve (AUC) of 0.915 (P< 0.05), sensitivity of 0.831, and specificity of 0. 892.Conclusion: Compared to conventional pulmonary function tests, IOS effectively identifies uncontrolled status in asthmatic children, particularly in younger patients, with higher sensitivity to small airway function changes. The model comprising R5+(R5-R20) +FeNO demonstrates clinical value in identifying uncontrolled status in asthmatic children.Keywords: impulse oscillometry, conventional pulmonary function, fractional exhaled nitric oxide, asthma control, children